Ciudadanía y globalización. El reto de un nuevo modelo para el pleno reconocimiento de los derechos de las personas - Andrade Quevedo, Karla Elizabeth (2017)
The current Nation-state model of citizenship that we manage has exhausted its action capability in this globalized world where the demos is no longer homogeneous, neither responds to ethnic and cultural factors. Today’s reality has converted the concept of citizenship in an exclusion element that inhibits people to fully exercise fundamental rights, just because they don’t have a territorial or blood link to the State where they live. This has provoked the appearance of second class citizens who don’t have the same rights even though they are part of the State and assume every obligation as citizens. Therefore, this has to change; a revolution in the citizenship concept is needed and we have to tie it up to more real and significant factors. Untie it from nationality and allow its material content to grow and extend to everyone who is really part of a State. Only an inclusive citizenship model allows full rights recognition, guarantees democratic legitimation and creates a real link between people and their State of residence. The only chance to move forward in fundamental rights recognition and be congruent with globalization needs, is to walk towards inclusive citizenship.